2020
DOI: 10.23960/jhptt.12120-25
|View full text |Cite
|
Sign up to set email alerts
|

LARVICIDAL AND ANTIFEEDANT ACTIVITIES OF CLOVE LEAF OIL AGAINST Spodoptera litura (F.) ON SOYBEAN

Abstract: Larvicidal and antifeedant activities of clove leaf oil against Spodoptera litura (F.) on Soybean. Economic losses due toinfestation by the soybean armyworm, Spodoptera litura can reach up to 100%. Some farmers often used insecticide to control thearmyworm. However, regular use of insecticide can cause several negative effects such as environmental pollution, residual toxicity,and health hazard for human. The objective of this research was to determine the larvicidal, antifeedant, and activities of cloveleaf o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Jumbo et al (2018) reported that, in a dosagedependent manner, the essential oils of S. aromaticum and Cinnamomum zeylanicum inhibited oviposition, hampered the emergence of offspring, and correspondingly slowed the growth rate of Callosobruchus maculatus. Similarly, essential oil extracted from clove leaves displayed strong larvicidal and antifeedant properties against third instar larvae of armyworm (Spodoptera litura) at a concentration of 2.0%, with LC 50 of 0.09% and LT 50 of 24.6 hours (Fateha et al, 2021). Further, 48 hours after treatment, 100% of adult Sitophilus zeamais and A. obtectus exposed to 17.9 and 35μL g-1 concentrations of clove essential oil were observed killed (Jairoce et al, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…Jumbo et al (2018) reported that, in a dosagedependent manner, the essential oils of S. aromaticum and Cinnamomum zeylanicum inhibited oviposition, hampered the emergence of offspring, and correspondingly slowed the growth rate of Callosobruchus maculatus. Similarly, essential oil extracted from clove leaves displayed strong larvicidal and antifeedant properties against third instar larvae of armyworm (Spodoptera litura) at a concentration of 2.0%, with LC 50 of 0.09% and LT 50 of 24.6 hours (Fateha et al, 2021). Further, 48 hours after treatment, 100% of adult Sitophilus zeamais and A. obtectus exposed to 17.9 and 35μL g-1 concentrations of clove essential oil were observed killed (Jairoce et al, 2016).…”
Section: Introductionmentioning
confidence: 98%